De geschiedenis van Brugge - Van Houtte, J. A. (Jan Albert), 1913-2002; Devliegher, Luc, 1927-; Van Acker, Frank, 1929-1992; Vanedewalle, André, ....- (Tielt : Lannoo, 1982)
Geïllustreerde historische beschrijving.
Includes bibliographical references and index.
Keywords: Bruges (Belgium) -- History; Brugge -- Geschiedenis